Analysis And Revitalization of Traditional Sports Policy as a Means of National Development in Preserving National Culture - Dedi Nofrizal; Ramadan Ramadan; Epenetus Giawa; Hafiz Yazid Lubis; Enggellina Gori; Benny Aprial M.; Herli Pardilla (Gladi : Jurnal Ilmu Keolahragaan, 2025)
Traditional sports face the risk of extinction due to globalization and lack of policy attention. This study analyzes the role of government policies in the development and preservation of traditional sports as part of national development and cultural heritage protection. Using a qualitative approach, data were collected through in-depth interviews, observations, and documentation involving community representatives and relevant government stakeholders. NVIVO 12 Plus was used for thematic data analysis, including reduction, presentation, conclusion drawing, and verification. The findings show that policy support positively impacts cultural identity, youth participation, and public awareness. Key strategies identified include curriculum integration in schools, traditional sports festivals and competitions, digital transformation of games, and cultural diplomacy. Strong collaboration among government, schools, communities, and youth is essential for sustainability. This study contributes to the development of inclusive, culturally rooted sports policies and highlights the potential of traditional sports in character education and the creative economy. It enriches the discourse on collaborative governance for heritage protection and offers insights into effective cultural preservation through sport. Continuous commitment is required to ensure that traditional sports not only survive but thrive as living traditions and national assets.